Full Spectrum of Postnatal Tooth Phenotypes in a Novel Irf6 Cleft Lip Model. (October 2016) - Chu, E.Y.; Tamasas, B.; Fong, H.; Foster, B.L.; LaCourse, M.R.; Tran, A.B.; Martin, J.F.; Schutte, B.C.; Somerman, M.J.; Cox, T.C.
Clefting of the lip, with or without palatal involvement (CLP), is associated with a higher incidence of developmental tooth abnormalities, including hypodontia and supernumerary teeth, aberrant crown and root morphologies, and enamel defects, although the underlying mechanistic link is poorly understood. As most CLP genes are expressed throughout the oral epithelium, the authors hypothesized that the expression of CLP genes may persist in the dental epithelium and thus, in addition to their earlier role in labiopalatine development, may play an important functional role in subsequent tooth patterning and amelogenesis. To address this, the authors generated a unique conditional knockout model involving the major CLP gene, Irf6, that overcomes the previously reported perinatal lethality to enable assessment of any posteruption dental phenotypes. A dental epithelium–specific Irf6 conditional knockout ( Irf6 -cKO) mouse was generated via a Pitx2 -Cre driver line. Dental development was analyzed by microcomputed tomography, scanning electron microscopy, histology, immunohistochemistry, and quantitative polymerase chain reaction. Irf6 -cKO mice displayed variable hypodontia, occasional supernumerary incisors and molars, as well as crown and root patterning anomalies, including peg-shaped first molars and taurodontic and C-shaped mandibular second molars. Enamel density was reduced in preeruption Irf6 -cKO mice, and some shearing of enamel rods was noted in posteruption incisors. There was also rapid attrition of Irf6 -cKO molars following eruption. Histologically, Irf6 -cKO ameloblasts exhibited disturbances in adhesion and polarity, and delayed enamel formation was confirmed immunohistochemically. Altered structure of Hertwig's epithelial root sheath was also observed. These data support a role for IRF6 in tooth number, crown and root morphology and amelogenesis that is likely due to a functional role of Irf6 in organization and polarity of epithelial cell types. This data reinforce the notion that various isolated tooth defects could be considered part of the CLP spectrum in relatives of an affected individual.